2019
DOI: 10.5994/jei.16.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Jasa penyerbukan serangga pengunjung bunga pada pertanaman stroberi di Ciwidey, Bandung

Abstract: Stroberi (Fragaria x ananassa Duch.) merupakan tanaman hortikultura yang penyerbukannya sebagian tergantung pada serangga. Studi dilaksanakan pada pertanaman stroberi di Ciwidey-Bandung, dengan tujuan untuk memperkirakan kontribusi dari serangga pengunjung bunga terhadap kesuksesan penyerbukan stroberi. Di dalam studi ini kontribusi tersebut dinilai dari kelimpahan spesies serangga pengunjung bunga dan durasi kunjungan pada bunga, serta efisiensi penyerbukan yang diukur dari jumlah akene yang berkemban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The bee A. cerana visited flowers for a shorter duration than the fly pollinator S. discolor. This indicated that bees were more efficient as insect pollinators than flies (Masyitah et al 2019). Bartomeus et al (2014) asserted that elevated pollinator visits influenced the augmentation of crop yields.…”
Section: A C Bmentioning
confidence: 99%
See 2 more Smart Citations
“…The bee A. cerana visited flowers for a shorter duration than the fly pollinator S. discolor. This indicated that bees were more efficient as insect pollinators than flies (Masyitah et al 2019). Bartomeus et al (2014) asserted that elevated pollinator visits influenced the augmentation of crop yields.…”
Section: A C Bmentioning
confidence: 99%
“…The A. cerana bee actively gathered pollen and nectar through direct contact between its mouthparts and the anthers while extracting the nectar from the base of the flower. Pollen was collected in the corbicles found on the hind limbs of the insect's body and in the hairs found on the ventral part of the abdomen (Masyitah et al 2019). S. discolor did not collect pollen and nectar but fed on pollen and nectar.…”
Section: A C Bmentioning
confidence: 99%
See 1 more Smart Citation
“…At that time, pollinators unintentionally could help plant distribute their pollen [5]. This process did not only help pollination but also bring more benefits, such as increasing the quantity and quality of fruits [6,7].…”
Section: Introductionmentioning
confidence: 99%